Community managed forests and forest protected areas: An assessment of their conservation effectiveness across the tropics - Porter-Bolland, L.; Ellis, E.A.; Guariguata, Manuel R.; Ruíz Mallén, I.; Negrete-Yankelevich, S.; Reyes García, Victoria (2011)
This paper assesses the role of protected and community managed forests for the long term maintenance of forest cover in the tropics. Through a meta-analysis of published case-studies, we compare land use/ cover change data for these two broad types of forest management and assess their performance in maintaining forest cover. Case studies included 40 protected areas and 33 community managed forests from the peer reviewed literature. A statistical comparison of annual deforestation rates and a Qualitative Comparative Analysis were conducted. We found that as a whole, community managed forests presented lower and less variable annual deforestation rates than protected forests. We consider that a more resilient and robust forest conservation strategy should encompass a regional vision with different land use types in which social and economic needs of local inhabitants, as well as tenure rights and local capacities, are recognized. Further research for understanding institutional arrangements that derive from local governance in favor of tropical forest conservation is recommended.